Spory wokól obrony przez kulturę w kontekście debat na temat wielokulturowości - Kania, Magdalena M. (Polityka i Społeczeństwo, 2020)
The main aim of this article is to introduce the concept of culture/cultural defence into the framework of current debates over multiculturalism. Culture defence is a relatively new legal strategy, which seeks to strengthen its own position as a formal strategy in criminal law, mainly in the common law system. It is based on the cognitive assumption that culture affects individuals’ perception of social reality to that extent that individuals could lack the capacity to act with the full ignorance of culturally given norms. The concept of culture defence will be juxtaposed to the different approaches to multiculturalism itself: to the concept of John Rawls’s theory of justice, to the concept of politics of difference as introduced by Charles Taylor, and to the politics of multiculturalism proposed by Will Kymlicka. This article reveals the question of legitimacy of culture defence as a crucial question bounded up with political philosophy, not exclusively embraced by the philosophy of law.